Dust sweeper robot with controller / Muhammad Irsyaduddin Ahmad Nazri - Ahmad Nazri, Muhammad Irsyaduddin (2024)
This research represents the development of a robot that helps cleaning the floor that called as Dust Sweeper Robot with Controller which has been equipped with an advance control system. The robot system incorporates key components such as Arduino Uno, L293D Motor Driver Shield, HC-05 Bluetooth Module, DC Motor, Servo Motor and Water pump. The real objective for the project is to design a very versatile cleaning robot which capable to do some efficient work of cleaning by sweeping and also mopping the dusty floor in any place at any time. The robot's mobility is facilitated by the integration of a 4 DC motor, controlled by the L293D motor driver shield, allowing the 2 DC motor for precise and agile movement. While the other 2 DC motor are employed to manipulate the sweeping mechanism, enabling targeted and adjustable cleaning angles. To enhance user interaction and control, a wireless communication system is established using the HC-05 Bluetooth module. This allows users to remotely control the robot's movements and cleaning functions through a dedicated mobile application or Bluetooth-enabled device. The system's versatility is further extended with the incorporation of a water pump, enabling the robot to perform wet cleaning tasks, enhancing its efficacy in different cleaning scenarios. The research details the design process, hardware configuration, and the development of the control algorithm governing the robot's movements. Experimental results demonstrate the effectiveness of the dust sweeper robot in efficiently cleaning diverse surfaces. This study contributes to the field of robotics by presenting a comprehensive solution for automated cleaning tasks with the integration of intelligent control mechanisms. The proposed system showcases the potential of combining Arduino-based technology with various actuators and sensors to create a versatile and user-friendly cleaning robot. The insights gained from this research pave the way for further advancements in the domain of smart cleaning robotics.